Adjusted automata learning algorithm for security protocol adaptive model checking - Jing YANG; Dan FAN; Yu-qing ZHANG (Tongxin xuebao)
Modifications and improvements for adjusted automata learning algorithms,which were enabled by recent developments.Adjusted automata learning algorithm La* is correct and efficient.It will be helpful to improve adaptive model checking efficiency,reduce the cost,solve state space explosion problem and resist many kinds of attack methods for security protocols.